Community Diagnosis Activities in Efforts to Reduce Hypertension Cases in the Working Area of Legok Health Center, Legok District, Tangerang District, Banten Province - Hansen, Hansen; Novendy, Novendy (PT Inovasi Pratama Internasional, 2024)
Background: Hypertension is one of the most common causes of heart disease, stroke, and kidney failure. Hypertension cases in Indonesia until 2018 were recorded at around 34.1%. There was an increase compared to 2013 which was 25.8%. The number of new cases of hypertension during July to September 2023 at the Legok Health Center is known to increase every month, from 63 to 77 cases with the highest cases in Babakan Village. From the mini-survey, it was found that knowledge about hypertension was still lacking. Objective: To increase public knowledge about hypertension as a whole in the working area of the Legok Health Center. Methods: A community diagnosis approach was used to identify problems using Blum's Paradigm. Problem prioritization was determined using non-scoring Delphi technique and the root cause of the problem was determined through fish-bone diagram. Data on intervention outcomes were obtained through pre and post test questionnaires. Monitoring was conducted using the plan-do-check-action (PDCA) cycle. Results: Based on the results of the analysis using the fishbone diagram, the main problem is lifestyle. The results of the activity obtained all participants scored ≥70 points on the post-test and blood pressure screening ≥140 and / or ≥90 was obtained in 10 people (35.71%). The nutritional status of under-weight was found in 2 people (7.14%), normal in 5 (17.86%), overweight in 3 (10.71%), obesity level 1 in 12 people (42.86%), and obese level 2 in 6 people (21.43%) and abdominal circumference ≥80 cm in 21 people (75%). Conclusion: Based on our intervention, it can be stated that our intervention is successful so that it is expected to reduce hypertension cases at the Legok Health Center